1992
DOI: 10.1128/mcb.12.9.3678
|View full text |Cite
|
Sign up to set email alerts
|

COT1, a gene involved in cobalt accumulation in Saccharomyces cerevisiae.

Abstract: The COT] gene of Saccharomyces cerevisiae has been isolated as a dosage-dependent suppressor of cobalt toxicity. Overexpression (10,13,27). Although the CUP1 protein has been shown to bind several metals (64), increased expression of the CUP1 gene confers tolerance only to copper and cadmium (27, 30).We describe the isolation of COT1, a gene that when overexpressed enables wild-type strains of S. cerevisae to grow in media containing as much as 20 mM CoCl2. Deletion of the COTI gene makes cells more sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
126
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(128 citation statements)
references
References 28 publications
1
126
0
1
Order By: Relevance
“…Whereas previous reports suggested that ZRC1 and COT1 primarily confer tolerance to zinc and cobalt ions respectively (8,12), it is now clear that under certain conditions, these genes are functionally redundant with respect to zinc. Zrc1 and Cot1 are both important determinants of zinc detoxification in zinc-replete yeast grown in high zinc, and both genes were implicated in the vacuolar storage of zinc in zinc-replete cells (13,14).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Whereas previous reports suggested that ZRC1 and COT1 primarily confer tolerance to zinc and cobalt ions respectively (8,12), it is now clear that under certain conditions, these genes are functionally redundant with respect to zinc. Zrc1 and Cot1 are both important determinants of zinc detoxification in zinc-replete yeast grown in high zinc, and both genes were implicated in the vacuolar storage of zinc in zinc-replete cells (13,14).…”
Section: Discussionmentioning
confidence: 77%
“…Our recent in vitro studies provided evidence that Zrc1 directly mediates vacuolar zinc transport, most likely via a zinc/H ϩ antiport mechanism (11). The COT1 gene encodes a related protein that may act analogously to Zrc1 in cobalt detoxification (8,12). Cot1 also contributes to zinc detoxification (13) and both Zrc1 and Cot1 appear to be required for sequestration of zinc in an intracellular storage compartment for later use under zinc-limiting conditions (14).…”
mentioning
confidence: 99%
“…The Zn-sensitive phenotype of the zrc1 ⌬ mutant was fully complemented by PtdMTP1. cot1 ⌬ mutants are hypersensitive to both Zn and Co, because COT1 mediates the efflux of both ions into the vacuole (Conklin et al, 1992;Li and Kaplan, 1998;Lyons et al, 2000). Interestingly, although PtdMTP1 complemented the cot1 ⌬ mutant phenotype when grown on Zn ( Figures 3C and 3D), PtdMTP1 failed to complement when grown on Co ( Figures 3E and 3F).…”
Section: Expression Of Ptdmtp1 In Yeast Confers Tolerance To Zn But Nmentioning
confidence: 92%
“…ZnT-1 is an integral membrane protein with a deduced length of 507 aa and is predicted to contain six transmembrane-spanning domains (11). It shares limited homology to the yeast cobalt transporter COT1 (15). The ZnT-1 sequence contains the motif (His-Gly) 8 in the large intracellular loop between membrane-spanning regions 4 and 5.…”
mentioning
confidence: 99%